Smart Protection pada Prototipe Gedung Asuransi Astra Berbasis Mikrokontroler - Masta, Putra Irfanda; Zulkarnaini, Zulkarnaini; Syofian, Andi; Warmi, Yusreni; Dewi, Arfita Yuana (TSAQOFAH, 2025)
The development of technology is carried out to support human needs to be more practical in life, one of which is in the field of security. Based on data obtained from the Central Statistics Agency regarding criminal statistics, theft is the most commonly occurring crime in Indonesia. This underpins this research, which aims to develop a building security system by utilizing several components, such as RFID sensors (Radio Frequency Identification), magnetic sensors, NodeMCU microcontroller, buzzer, and the Blynk application on mobile phones to control and receive notifications from the device. The creation of this tool is intended to maximize the use of the Blynk application on mobile phones and synergize with the NodeMCU microcontroller, thus creating a useful, creative, and innovative device. The result of this research is the creation of an intelligent system in the form of building security through a mobile application, which can control and provide warning notifications when the sensor detects unauthorized persons entering the building.